Pengembangan Strategi Pengelolaan Sungai Ciujung, Provinsi Banten Menggunakan Metode AHP - Shofiyatul Afidah; Sutrisno Anggoro; Sudarno Sudarno (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Afidah S, Anggoro S, Sudarno S. 2020. Development of strategy management ciujung river use AHP Method. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Ciujung River is one of the largest rivers in Banten Province, resident in Ciujung River basin still use water from Ciujung to fulfill their daily needs, the other designation of Ciujung river is as receiver industrial, domestic and agricultural waste, until 2020 result of monitoring Ciujung river was polluted. This study aims to develop a management strategy for Ciujung River. Pollution index method is used to determined water quality status of Ciujung River, AHP method is used in determined priority of criteria and sub-criteria in management of Ciujung River. This study began with calculated pollution index in 2017-2019, next step is AHP hierarchy arrangement and the pairwise comparison matrix, then distributed questionnaires to 10 respondents and data was analised using Expert Choice 11 software. Results of analysis use AHP show that the most influential criteria in managing Ciujung River is goverment policy, the most influential management objective was to improve the quality of Ciujung River water, and the most influential goverment policy was law enforcement. Ciujung river strategy management that must be carried out by goverment is law enforcement to improve water quality.